Characterization and expression of fungal defensin in Escherichia coli and its antifungal mechanism by RNA-seq analysis - Chen, Yu-Pei; Li, Yingying; Chen, Fangfang; Wu, Hongtan; Zhang, Shudi (Frontiers in Microbiology, 2023)
Invasive fungal infections (IFIs) are fatally threatening to critical patients. The fungal defensin as an antifungal protein can widely inhibit fungi. In this study, eight antifungal genes from different filamentous fungi were optimized by synonymous codon bias and heterologously expressed in Escherichia coli. Only the antifungal protein (AFP) from Aspergillus giganteus was produced, whereas the AFP from its mutation of the chitin-binding domain could not be expressed, thereby suggesting the importance of the motif for protein folding. In addition, the recombinant AFP (rAFP, 100 µg/mL) pre-heated at 50℃ for 1 h effectively inhibited Paecilomyces variotii CICC40716 of IFIs by 55%, and no cell cytotoxicity was observed in RAW264.7 cells. After being pre-heated at 50℃ for 8 h, the fluorescence emission intensity of the rAFP decreased and shifted from 343 nm to 335 nm. Moreover, the helix and β-turn of the rAFP gradually decreased with the pre-heated treatment temperature of 50℃ via circular dichroism spectroscopy. Propidium iodide staining revealed that the rAFP could cause damage to the cell membrane. Moreover, the corresponding differentially expressed genes (DEGs) for downregulation such as amino sugar and nucleotide sugar metabolism, as well as mitogen-activated protein kinase (MAPK) signaling pathway involved in the cell wall integrity were found via the RNA-seq of rAFP treatment. By contrast, the upregulated DEGs were enriched in response to the oxidative stress of Biological Process by the Gene Ontology (GO) database. The encoding proteins of laccase, multicopper oxidase, and nitroreductase that contributed to reactive oxygen species (ROS) scavenging could be recognized. These results suggested that the rAFP may affect the integrity of the cell wall and cell membrane, and promote the increase in ROS, thereby resulting in fungal death. Consequently, drug development could be based on the inhibitory effect of the rAFP on IFIs.